Validation of energy-related vacuolar subunit gene Pc_PVA1 from wild halophyte Pc in salt sensitive commercial rice, BR75 - Anonna, Eera Ashrafy (Brac University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology 2020.